A 5‑year evaluation of chemoprophylactic treatment in elementary school children with subclinical leprosy - Linda Astari, - (Spandidos Publications, 2021)
Subclinical leprosy is an infectious disease in which the immune system remains infected with Mycobacterium leprae (M. leprae). The progress of subclinical leprosy to clinical cases within 1 year of infection is 1.5%, with an increase to 6% in the following 4 years. Rifampicin is frequently used for prevention of leprosy, and clarithromycin has a bactericidal effect on M. leprae. Thus, the combination of both is expected to improve disease control in patients with subclinical leprosy. The aim of the present study was to evaluate the efficacy of a chemoprophylactic treatment involving rifampicin and clarithromycin against subclinical leprosy in elementary school children from endemic areas of East Java over a 5‑year period. The study was performed between 2011 and 2015. Samples were collected from 2,548 healthy elementary school children in Nguling (Pasuruan) and Raas (Sumenep), and analysed using ELISA for anti‑PGL (phenolic glycolipid)‑1 IgM antibodies. Children who were seropositive for anti‑PGL‑1 IgM antibodies received a chemoprophylactic regimen consisting of rifampicin (300 mg/day) and clarithromycin (250 mg/day) daily for the initial 10 days, followed by the same regimen every 2 weeks for 3 months. Clinical and serological evaluations were performed annually for 5 years. Amongst the 2,548 healthy elementary school children, 200 were seropositive. The anti‑PGL‑1 IgM antibody levels significantly decreased between 2011 and 2015 in Nguling (from 1,066.7 to 137.4 U/ml) and Raas (from 773.1 to 563.4 U/ml), the levels decreased every year. In addition, the proportion of patients with decreased anti‑PGL‑1 IgM antibody levels was consistently higher than patients with increased anti‑PGL‑1 IgM antibody levels in all periods, except during 2013‑2014, in Nguling and Raas. Chemoprophylactic treatment involving rifampicin and clarithromycin may thus be effective against subclinical leprosy amongst elementary school children.